Strengthening the Pancasila Student Profile Through Hizbul Wathan Extracurricular Activities - Kartika Putri, Riva Wahyu; Suyitno, Suyitno (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2023)
The background of the study is the need for better character in primary school students. Accordingly, this study aims to describe how to strengthen the Pancasila student profiles through Hizbul Wathan’s extracurricular activities at SD Muhammadiyah Condongcatur. This is a qualitative descriptive study. The subjects were the vice principals, Hizbul Wathan coaches, and students. The data were collected through observation, interviews, and documentation. The data were validated using source and technique triangulation and analyzed through data collection, reduction, presentation, and conclusion drawing. The study results indicate that strengthening the Pancasila student profiles through Hizbul Wathan’s extracurricular activities at SD Muhammadiyah Condongcatur has been conducted through six main dimensions. The supporting factors are the sufficient and certified Hizbul Wathan coaches, proper facilities and infrastructure, Hizbul Wathan team, curriculum, school policies, presentation of materials, examples from Hizbul Wathan coaches, and parents. Meanwhile, the inhibiting factors are the number of students, slow absorption of materials, character-long habituation process, parents, religion, students’ environment, facilities and infrastructure, and the quality of Hizbul Wathan coaches.